Antifungal activity of some stem extracts against seed-borne pathogenic fungi - Pawar, B T (Journal of Phytology, 2011)
Plant extracts are being used to control the diseases since last several years. Extracts of the various plant parts like leaf, stem, root, fruit and seeds are found to be effective against seed-borne pathogenic fungi. The in vitro studies have been performed by using cup-plate method to examine the antifungal activity of some stem extracts. Stem extracts of 9 plants were screened against 5 seed-borne pathogenic fungi viz. Alternaria alternata, Aspergillus niger, Curvularia lunata, Fusarium moniliforme and Trichoderma viride. Out of 9 stem extracts, 6 stem extracts showed antifungal activity. The extract of Azadirachta indica showed maximum activity; while minimum activity was observed with Callistemon rigidus against the fungi under investigation. These plant extracts can possibly be exploited in the management of seed-borne pathogenic fungi to prevent biodeterioration of seeds in an eco-friendly way. <!–EndFragment–>